Relaksasi Otot Progresif Dalam Meningkatkan Kualitas Tidur: Review Sistematik - Steffy Putri Amanda (LPPM STIKES Guna Bangsa, 2019)
Background: Untreated sleep quality can bring changes that can affect both physically and psychologically so that it can reduce sleep quality in menopausal women, one of the non-pharmacological management in improving sleep quality is progressive muscle relaxation by reducing muscle tension, eliminating fatigue so as to improve quality sleep in menopausal women. Objective: to determine the effectiveness of progressive muscle relaxation in improving sleep quality. Method: A systematic review through review of maternity nursing articles to identify the effect of progressive muscle relaxation in improving sleep quality in menopausal women. The article inclusion criteria used were the effect of progressive muscle relaxation in improving sleep quality, while the exclusion criteria ie articles were not full text. Search articles are accessed from databases, namely: Sciencedirect, Pubmed, JKI, JKD. Articles that meet the inclusion criteria are collected and examined systematically. Search for literature published from 2015 to 2018. the article search process gets 4 articles that meet the requirements for inclusion and exclusion criteria. Results: in this systematic review shows that progressive muscle relaxation can improve sleep quality. Conclusion: Progressive muscle relaxation can improve sleep quality